2021
DOI: 10.1097/md.0000000000026301
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of complete blood count constituents in gestational diabetes mellitus

Abstract: Background (Trial Design): The incidence rate of gestational diabetes is high. In the long run, it harms the health of both the mother and child. In order to understand the distribution of hematological cells with gestational diabetes mellitus (GDM), a longitudinal cohort study was conducted from 2012 to 2018. Methods: A longitudinal case control study of 1860 pregnant women was conducted between 2012 and 2018. Data of hematological parameters at 11 time points of gesta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…Therefore, physiological changes in Han Chinese and SEA women may have similarities. This data is also consistent with other sources that state that women are in a hypercoagulable state in the second trimester [ 20 ].…”
Section: Pathophysiology Of Uninfected Versus Infected Pregnant Womensupporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, physiological changes in Han Chinese and SEA women may have similarities. This data is also consistent with other sources that state that women are in a hypercoagulable state in the second trimester [ 20 ].…”
Section: Pathophysiology Of Uninfected Versus Infected Pregnant Womensupporting
confidence: 92%
“…For the other articles, one from SEA includes a case report from Singapore [ 26 ]. Research based in Asia consists of that from China [ 20 ] only. Research based on populations outside of Asia was from Mexico [ 17 ], Spain [ 22 ], and the United Kingdom [ 24 ].…”
Section: Pathophysiology Of Uninfected Versus Infected Pregnant Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study among 1860 pregnant Chinese women found approximately equivalent levels in WBC between the GDM and non-GDM groups during gestational weeks 25–28, and then WBC in the GDM group decreased until delivery, whereas WBC levels in the non-GDM group continued to increase during pregnancy and peaked at week 1 postpartum. 17 Another study conducted in Turkey enrolled 269 pregnant women found no significant difference in WBC levels between the GDM and non-GDM group during 24–28 weeks of gestation. 32 However, the mechanism of the slight decrease of WBC in GDM women has not been elucidated, and it may be related to the inflammation and insulin resistance in middle pregnancy.…”
Section: Discussionmentioning
confidence: 96%
“…With remarkable success, a variety of novel drug delivery systems have been tested in recent years, as indicated in Table 3, aiming to enhance the physicochemical characteristics of UA and support its therapeutic usage. In addition to making hydrophobic medicines more soluble and bioavailable, they also modify drug release 82 . Nano delivery was studied by Manayi et al 46 .…”
Section: Novel Drug Delivery System Of Uamentioning
confidence: 99%